(untitled) (Bangladesh Journal of Botany, 2023)
In vitro propagation of red rose [Rosa pisiformis (Christ.) D. Sosn.] has great importance in rapid proliferation of species with medicinal features and in culture of healthy plants free from deseases. After a succesfully pre-sterilization procedure, experiments were maintained by two-phase: multiplication phase and rooting of microshoots phase. Micropropagation of Rose was improved, using its nodal segments under different combination of BAP (0, 1.0, 2.0, 0.6 mg/l), NAA (0, 0.1, 0.2, 0.01 mg/l) on Driver and Kuniyuki (DKW) and MS medium in multiplication phase and using distinct compositions of IBA (0, 1.0, 3.0, 5.0 mg/l) and DKW medium in rooting phase. The maximum number of shoots/per plant (22.6) with the highest number of leaves (222.6) were obtained in DKW medium supplemented with 0.6 mgl-1 BAP and 0.01 mg/l NAA. The leaf explants were also used to occur callus in MS with different combinations of BAP and NAA. Good callus formation was obtained with 1:2 ratio of BAP:NAA combination in MS medium. Furthermore, the highest root induction (100%) was achieved in DKW medium consisting of 1 mg/l IBA. The rooted plantlets were transferred to the field after acclimatized in greenfield conditions. The present investigation presents an in vitro protocol for R. pisiformis. Bangladesh J. Bot. 52(4): 949-958, 2023 (December)